INVESTMENT ANALYSIS OF GOLD MINING PROJECT (CASE STUDY OF PT XYZ) - Noerman, Iqbal
Looking at global and domestic conditions, gold demand is expected to continue to increase, driven by the jewelry, investment, central bank, and technology sectors. Gold jewelry is the largest source of annual demand for gold by sector. India and China are by far the most prominent jewelry markets, together accounting for more than 50% of total global demand. The Asian and Middle Eastern markets are dominated by demand for purer and higher-carat gold. In addition, gold plays a significant role in global central bank reserves, and they are substantial holders of gold. The 2008 financial crisis prompted a fundamental change in central bank attitudes towards gold, prompting a reassessment of its role and relevance in reserve asset management. Central banks in emerging markets have increased their official gold purchases, while European banks have stopped selling, and the sector is now a significant source of annual gold demand. In the investment sector, investors of all types are beginning to accept gold as a reliable and tangible long-term store of value compared to other assets, while in the technology sector, the electrification trend is supporting gold demand in this sector, with most types of semiconductor chips using the metal either as a coating or in the form of thin wires.